Living donor liver transplantation: risk factors associated with anxiety symptoms in an Egyptian sample. Issue 4 (October 2016) - ElGhonemy, Soheir H.; Hashem, Reem; ElMissriy, Marwa; Hatata, Hisham; ElSerfei, Doha; Ali, Rami
Abstract : Background: Living donor liver transplantation has become an established treatment for end-stage liver disease. It remains unclear whether the donation process is psychologically harmful or beneficial. Aim: This prospective study investigated the rate of anxiety and its severity along 3 months of follow-up and to determine the associated possible risk factors after donation. Patients and methods: A total of 65 potential donors were investigated using the General Health Questionnaire, the Structured Clinical Interview DSM-IV Axis I diagnosis (SCID-I), and the Eysenck Personality Questionnaire. Only 33 patients fulfilled the inclusion criteria (actual donors). Thus, they were assessed along three visits during the 3-month period using the Taylor Manifest Anxiety Scale. Results: Data revealed that 24% of actual donors experienced anxiety symptoms at the end of first week after donation. The rate of anxiety declined over the consecutive visits, wherein almost 81.1% of the studied sample was anxiety-free at the last visit after 3 months. Linear regression analysis denoted that a higher risk for emergence of anxiety is associated with female sex, younger age, being married, having either preparatory or university education, being a housewife, engagement in managerial job, and the recipient being the donor's father. Moreover, donors who scored higher in neuroticism, psychoticism, and impulsivity were more prone to experience anxiety symptoms after donation. Conclusion: Psychiatric assessment for living donor liver transplantation during the postdonation periods allows early identification of anxiety symptoms and recognition of the possible risk factors that may subject donors to experience anxiety after donation.